2017
DOI: 10.3389/fcimb.2017.00457
|View full text |Cite
|
Sign up to set email alerts
|

Application of ImmunoScore Model for the Differentiation between Active Tuberculosis and Latent Tuberculosis Infection as Well as Monitoring Anti-tuberculosis Therapy

Abstract: Tuberculosis (TB) is a leading global public health problem. To achieve the end TB strategy, non-invasive markers for diagnosis and treatment monitoring of TB disease are urgently needed, especially in high-endemic countries such as China. Interferon-gamma release assays (IGRAs) and tuberculin skin test (TST), frequently used immunological methods for TB detection, are intrinsically unable to discriminate active tuberculosis (ATB) from latent tuberculosis infection (LTBI). Thus, the specificity of these method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Besides, TBAg/PHA ratio was helpless in identifying ATB with negative T-SPOT results due to its computational limitations. Several studies have demonstrated that the combination of multiple indicators could promote ATB diagnosis (31,32). Accordingly, we speculate that the use of the combination of lymphocyte non-specific function (non-specific marker) and T-SPOT (TB-specific marker) has the potential to improve rapid differential diagnosis between ATB and LTBI.…”
Section: Introductionmentioning
confidence: 94%
“…Besides, TBAg/PHA ratio was helpless in identifying ATB with negative T-SPOT results due to its computational limitations. Several studies have demonstrated that the combination of multiple indicators could promote ATB diagnosis (31,32). Accordingly, we speculate that the use of the combination of lymphocyte non-specific function (non-specific marker) and T-SPOT (TB-specific marker) has the potential to improve rapid differential diagnosis between ATB and LTBI.…”
Section: Introductionmentioning
confidence: 94%
“…Regarding the possible use of biomarkers in the field, considering the TPPs recommended by FIND/WHO, the sensitivity and specificity achieved by the combination of IFN-γ, IP-10, ferritin and 25(OH)D were optimal (Denkinger et al, 2015). In recent years, two case-control studies presented two models for the diagnosis of TB in children with minimal TPPs higher than those reached in this study for the development of a new diagnostic test (Armand et al, 2014; Zhou et al, 2017). However, they were not able to discriminate between active TB and LTBI cases.…”
Section: Discussionmentioning
confidence: 89%
“…LASSO is a regression analysis method that performs both variable selection and regulation to enhance the prediction accuracy and interpretability of the statistical model it produces (Friedman et al, 2010 ; Ciuperca, 2012 ). It can effectively avoid the problems of over-fitting and high correlation in the least squares estimation, and solve the problem of multicolinearity in regression analysis (Zhou et al, 2017 ; Zhang et al, 2018 ). LASSO has been widely used in many fields, such as the prediction of disease outcomes (Tang et al, 2018 ) and genome-wide (Waldmann et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%